2003
DOI: 10.1002/ardp.200300809
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Antibacterial Evaluation of Novel Imidazo[2′, 1′:5, 1]‐1, 2, 4‐triazolo[4, 3‐c]‐quinazoline Derivatives of 5‐Thioxo‐1, 2, 4‐triazole, 4‐Oxothiazolidine, and their Open‐chain Counterparts

Abstract: Two novel series of imidazo[2', 1':5, 1]-1, 2, 4-triazolo[4, 3-c]quinazolines bearing 5-thioxo-1, 2, 4-triazoles, 6a-f, and 4-oxothiazolidines, 7a-f, were synthesized from corresponding thiosemicarbazide derivatives, 5a-f. The stepwise methodology applied to the preparation of compounds 5a-f was initiated with reaction of the parent 3-amino-1, 2, 4-triazolo[4, 3-c]quinazolines, 2, with ethyl 2-chloroacetoacetate resulting in annelation of the imidazole ring to give esters, 3a-c. However, hydrazinolysis of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…IR spectrum showed five absorption bands characterized of acetyl groups around 1730-1754 cm −1 and a broad band for NH group at 3225 cm −1 . Its 1 H NMR spectrum gave data with supports assigned structure and showed that the signals around δ 1.86-2.17 supported for five acetyl group On the other hand, the reaction of compound 4 with 2-oxo-N -(4-sub-phenyl)-propane hydrazonoyl chloride 1b-e under the same reaction condition afforded 5-acetoxy-4-(D-arabino-1, 2, 3, 4-tetraacetoxy-butyl)-3 -acetyl-5 -phenyl/(sub-phenyl)-spiro-[1, 3]-thiazolidine-2,-2 - [1,3,4]thiadiazole 8b-e. The structures of 8b-e were deduced on the basis of analytical and spectral data.…”
Section: Chemistrymentioning
confidence: 96%
See 3 more Smart Citations
“…IR spectrum showed five absorption bands characterized of acetyl groups around 1730-1754 cm −1 and a broad band for NH group at 3225 cm −1 . Its 1 H NMR spectrum gave data with supports assigned structure and showed that the signals around δ 1.86-2.17 supported for five acetyl group On the other hand, the reaction of compound 4 with 2-oxo-N -(4-sub-phenyl)-propane hydrazonoyl chloride 1b-e under the same reaction condition afforded 5-acetoxy-4-(D-arabino-1, 2, 3, 4-tetraacetoxy-butyl)-3 -acetyl-5 -phenyl/(sub-phenyl)-spiro-[1, 3]-thiazolidine-2,-2 - [1,3,4]thiadiazole 8b-e. The structures of 8b-e were deduced on the basis of analytical and spectral data.…”
Section: Chemistrymentioning
confidence: 96%
“…Thus, the IR spectra for 8b-e revealed the presence of CO group at 1750 cm −1 , and 13 C-NMR showed signals corresponding to N -acetyl groups around 25 ppm for methyl group and 185 ppm for carbonyl group. Also, the reaction of compound 4 with chloro-(4-tolylhydrazono)-ethylacetate 1f afforded 5-acetoxy-4-(D-arabino-1, 2, 3, 4-tetraacetoxybutyl)-3 -ethylcarboxylate-5 -(4-tollyl)-spiro- [1,3]thiazolidine-2,2 -[1,3,4]thiadiazole 8f. The IR spectrum of 8f revealed the presence of C=O (ester) at 1705 cm −1 .…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…[3]. Some recent publications are devoted to the search of chemotherapeutics among condensed quinazolines, in particular benzimidazo [1,2-c]-, benzthiadiazolimidazo [1,2-c]-, triazolo [1,5-c]-, imidazo, [1,2,4]triazolo [4,3-c]-, triazino [2,3-c]quinazolines [1,2,4,5,7,8,10,[13][14][15][16][17][18]. Highly effective antimicrobial, antifungal, anticancer agents have been found among the compounds mentioned.…”
mentioning
confidence: 99%